2018
DOI: 10.1053/j.gastro.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Competence in Endoscopic Ultrasound and Endoscopic Retrograde Cholangiopancreatography, From Training Through Independent Practice

Abstract: In this prospective multicenter study, we found that although competence cannot be confirmed for all AETs at the end of training, most meet QI thresholds for EUS and ERCP at the end of their first year of independent practice. This finding affirms the effectiveness of training programs. Clinicaltrials.gov ID NCT02509416.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 39 publications
1
71
0
2
Order By: Relevance
“…In this study, pain associated with insertion was reduced and plateaued after 70 procedures and approximately 3 months of experience. Studies of endoscopy learning curves showed that in the case of EUS, a certain level of technical competence was achieved after 50 to 75 procedures [17][18][19]. In this study, a comparable level of technical competence was reached in accordance with previous studies.…”
Section: Itt Analysissupporting
confidence: 90%
“…In this study, pain associated with insertion was reduced and plateaued after 70 procedures and approximately 3 months of experience. Studies of endoscopy learning curves showed that in the case of EUS, a certain level of technical competence was achieved after 50 to 75 procedures [17][18][19]. In this study, a comparable level of technical competence was reached in accordance with previous studies.…”
Section: Itt Analysissupporting
confidence: 90%
“…This approach to assessing learning curves and competence has been widely described in healthcare (cataract surgery, arthroscopy, anesthesia, and endoscopic procedures). 2,[11][12][13][14][15][16][17] Success was defined as a TEESAT score of 1 (no assistance) or 2 (minimal verbal cues) whereas a score of 3 or 4 was considered a failure. For the overall global rating, a score of 3 or 4 represented success.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The results of Phase 2, to measure outcomes during the first year of independent practice using established quality indicators in EUS and ERCP for AETP graduates who received continuous structured feedback, have been published separately. 2 Data from Phase 1 were used to address the primary aim of this study. Approval from the Institutional Review Board or the Human Research Protection Office at each site involved was obtained (ClinicalTrials.gov: NCT02509416) and signed informed consent was obtained from all AETs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations